Hydnopolyporus fimbriatus (Fr.) D.A. Reid mushroom: phytochemical screening, antioxidant activity, total flavonoid and total phenolic compounds - Menezes Filho, Antonio Carlos Pereira de; Ventura, Matheus Vinicius Abadia; Batista-Ventura, Helen Regina Fernandes; Porfiro, Cinthia Alves; Teixeira, Marconi Batista; Soares, Frederico Antônio Loureiro; Taques, Aparecida Sofia; Alves, Ivan; Castro, Carlos Frederico de Souza (Brazilian Journal of Science, 2022)
Hydnopolyporus fimbriatus is a species of mushroom of the Meripilaceae Jülich family found in some regions of Central and South America. This study aimed to evaluate the qualitative phytochemical composition, the antioxidant activity in the reduction of DPPH and hydroxyl free radicals and to determine the flavonoid contents and total phenolics in the ethanolic extract of the mushroom H. fimbriatus. The ethanolic extract was prepared and lyophilized. Qualitative phytochemical prospection assays were performed for different groups of organic compounds. The antioxidant assay was carried out in the reduction of the 2,2-diphenyl-1-picrylhy-drazyl free radical and in the reduction of the hydroxyl free radical by colorimetric methods. The ethanolic extract of H. fimbriatus positively exhibited several phytochemical groups, moderate antioxidant activity in reducing free radical DPPH 101.09 µ mL-1, high hydroxyl radical reducing activity 87.51% and potential total phenolic content 20.15 mg GAE 100 g-1 of dry extract. Flavonoids content was not observed possibly due to the colorimetric method using aluminum chloride. With these results, it was possible to characterize the ethanolic extract of the vegetative part of Hydnopolyporus fimbriatus. New studies should be carried out in an attempt to develop a quantitative method of total flavonoids as well as test the extract in other biological models, thus being able to develop new drugs or products for agricultural use.